Studi Efektivitas Koagulan Kitosan-Kapur Dalam Menurunkan COD, MBAS dan Fosfat pada Limbah Laundry - Fitriyah Fitriyah; Nur Fatimah; Tauny Akbari (Jurnal Serambi Engineering, 2023)
Abstract. Environmental pollution that is often encountered in daily life that comes from laundry waste. Laundry waste includes pollutants or substances that pollute the environment because in it there is a substance called linear alkylbenzene sulphonate (LAS). LAS is a detergent that is classified as hard to brake down by microorganisms (non-biodegradable) so that it can cause environmental pollution. One method that is often used in laundry wastewater treatment is coagulation using chitosan and lime as a coagulant. The purpose of this study was to analyze the efficiency and effectiveness in reducing pollutant levels in laundry waste using chitosan-lime coagulant. This study used a completely randomized design with 200 mg/L chitosan and 0.1-0.5 g lime. The test parameters used were COD, MBAS, and phosphate. Data were analyzed using calculation of efficiency and effectiveness of reduction, linear regression, and one-way ANOVA test. The results showed that under the best conditions, chitosan 200 mg/L and lime as much as 3.5 g resulted in a reduction efficiency of 68.52%, 9.15%, and 92.44%. Chitosan-lime is effective in reducing MBAS and phosphate levels to quality standard, but chitosan-lime coagulant is less effective in reducing COD levels because it still exceeds the the established quality standards